2017
DOI: 10.1016/j.ijid.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, comparative study of severe neurological and uncomplicated hand, foot and mouth forms of paediatric enterovirus 71 infections

Abstract: EV-A71 is an important cause of encephalitis in the Asia-Pacific region. Further studies to determine the risk factors associated with severe EV-A71 disease are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
10
1
1
Order By: Relevance
“…HFMDs caused by enteroviruses, such as CVA16 and EV71, are a group of infectious disease that affects millions of people globally, especially children under the age of 5 25 . Severe HFMDs are often associated with aseptic meningitis, brain stem encephalitis, and acute flaccid paralysis and can be fatal 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…HFMDs caused by enteroviruses, such as CVA16 and EV71, are a group of infectious disease that affects millions of people globally, especially children under the age of 5 25 . Severe HFMDs are often associated with aseptic meningitis, brain stem encephalitis, and acute flaccid paralysis and can be fatal 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, our study found that some clinical features, such as rash, mouth ulcers, and fever, are related to coxsackieviruses. A prospective cohort study conducted in Cambodia reported that EV-A71 was associated with severe clinical signs and symptoms among HFMD-infected children, particularly those with nervous system complications [ 51 ]. EV-A71 is a predominant serotype of an HFMD outbreak in Spain and is associated with severe clinical signs such as brainstem symptoms [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although HFMD is typically a mild illness, severe complications can sometimes occur. These include encephalitis, meningitis, acute flaccid paralysis, cardiorespiratory failure and can be fatal ( Figure 1 ; Crabol et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%